Land-use differences modify predator-prey interactions and Acacia vegetation in a hyperarid ecosystem. (September 2021) - Lewin, Amir; Erinjery, Joseph J.; le Polain de Waroux, Yann; Tripler, Effi; Iwamura, Takuya
Abstract: Dryland agriculture has extensive impacts on surrounding ecosystems through its unintentional provision of food and water resources to local wildlife. We analyzed the response of a predator community of jackals, wolves and foxes to land-management choices, and how that response in turn affects native gazelles and Acacia vegetation in the Arava Valley of Israel. This hyperarid region is characterized by contrasting regimes comprising privatized (Moshavim) and communal (Kibbutzim) agricultural settlements, which provides ideal conditions for evaluating how land-management differences translate into crop choices, affecting resource availability and ecosystem changes. Integrating multi-year field observations of predators and gazelles with agricultural datasets, we show that shifts in land-use strategies have cascading ecological impacts. This is evident in the association of date orchards, an expanding land use especially in Kibbutzim, with shifts in the geographical and seasonal distributions of predators. Increased predator presence due to resource availability has displaced gazelles farther from settlements, subsequently impacting Acacia seed dispersal and recruitment. Considering the global expansion of dryland agriculture, the evidence of such socio-ecological cascading effects suggests the necessity to approach agricultural management at the landscape scale in desert regions. Highlights: Land management practices have cascading ecological impacts in hyperarid regions. Invasive jackals have expanded their distributions tied to agricultural resources. Predator communities are modified by bottom-up and top-down processes. Predator changes have in-turn displaced native gazelle farther from settlements. Shifting gazelle distributions may impact Acacia vegetation by reduced recruitment.